A Descriptive Study of the Critical Thinking Skills of Social Science at Junior High School - Sri Hapsari (Journal of Education and Learning (EduLearn), 2016)
The significance of the research is to seize a description of critical thinking students at a Junior High School at South Tangerang, Indonesia. It uses a descriptive statistic method to describe a more specified critical thinking student. Nowadays, learning process has been valued as non-critical thinking method to students. Whereas, by the critical thinking there will be the activity of thinking process to conclude. It has needed to be drilled since it had been early time to students to solve the problems. It gets social science critical thinking of 401 students. It is measured by the indicators of interpretation, analysis, evaluation, explanation, and inference. The results indicate the students skill in interpretation, analysis, explanation, and inference at a high level whereas it needs to create learning process of critical thinking students to do the evaluation at a medium level creating the hard worker and problem solver students.